Array Antenna TRM Failure Compensation Using Adaptively Weighted Beam Pattern Mask Based on Genetic Algorithm - Jung-Hoon Han; Sang-Ho Lim; Noh-Hoon Myung (IEEE antennas and wireless propagation letters, 2012)
Digital beamforming array antenna systems are installed outdoors for long periods of time. When a transmitter/receiver module (TRM) error occurs, the beam pattern is distorted. In this case, resynthesizing the optimal beam pattern with all functioning TRMs, without failed TRM, is preferable to TRM repair or replacement. This letter proposes an algorithm for resynthesizing the optimal beam pattern from the distorted beam pattern using an adaptively weighted beam pattern mask based on a genetic algorithm. The proposed algorithm allows improved resynthesis flexibility and accuracy and increased calculation speed. Several beam patterns are also examined utilizing the proposed algorithm. The proposed TRM failure compensation algorithm provides a cost-effective and less time-consuming solution for repairing the digital beamforming antenna systems.